2021
DOI: 10.1097/icl.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Corneal Deformation Response Parameters by Dynamic Ultra High-speed Scheimpflug Imaging in Normal and Keratoconus Eyes

Abstract: To assess the repeatability of corneal dynamic response (CDR) parameters in normal and keratoconus (KC) eyes using ultra high-speed Scheimpflug imaging. Methods: Prospective, comparative, observational study, including eyes of 112 patients that underwent high-speed Scheimpflug imaging analysis (Corvis ST, OCULUS). Twenty-one CDR parameters were evaluated to asses repeatability using: coefficient of repeatability (CR), coefficient of variation, intraclass correlation coefficient (ICC) and within-subject SD. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…19,27 Thus, it has been reported that the reliability is comparable in healthy eyes or in eyes with mild or moderate KC, which was shown in 2 different comparison studies. 28,29 In addition, this study investigated 2 new parameters, the SSI and the CBiF, whose repeatability was investigated in KC for the first time. The CR, CoV, and ICC for the SSI were between 0.17 and 0.22, 6.16% and 6.67%, and 0.886 and 0.913 (for both groups), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…19,27 Thus, it has been reported that the reliability is comparable in healthy eyes or in eyes with mild or moderate KC, which was shown in 2 different comparison studies. 28,29 In addition, this study investigated 2 new parameters, the SSI and the CBiF, whose repeatability was investigated in KC for the first time. The CR, CoV, and ICC for the SSI were between 0.17 and 0.22, 6.16% and 6.67%, and 0.886 and 0.913 (for both groups), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of corneal biomechanics recently gained space as a hot topic in ophthalmology mainly due to its wide applications ( Roberts etal., 2014 ). Corneal biomechanical properties were known to assist with detecting corneal diseases ( Vinciguerra et al, 2017a ; Reinprayoon et al, 2021 ; Ziaei et al, 2021 ; Henriquez et al, 2022 ), predicting refractive outcomes before corneal refractive surgery ( Chen et al, 2018 ), judging different protocols of collagen crosslinking treatments ( Greenstein et al, 2012 ), and even selecting intracorneal ring implants ( Bao et al, 2016 ; Shen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Corvis ST ® measured more dynamic corneal biomechanical parameters with high repeatability [39]. The results of the study of Lin et al showed that several baseline CST parameters associated with AXL elongation and the related parameters differed after DISC and OK lens treatments [37].…”
Section: Discussionmentioning
confidence: 99%